Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor
Die Extrusion stellt das mengenmäßig dominante Verarbeitungsverfahren für thermoplastische Kunststoffe dar. Daher gibt es starke Bestrebungen in diesem Bereich hin zu einer höheren Wirtschaftlichkeit, welche beispielsweise durch höheren Massedurchsatz bei gleichbleibender Maschinengröße erreicht werden kann, oder aber auch im Hinblick auf eine Kreislaufwirtschaft die Bestrebung hin zu einer materialschonenden Verarbeitung. Beide Bestrebungen erfordern spezielle Schneckenkonzepte. Hierunter fallenWave- Schnecken, welche in beiden Bereichen ein vorteilhaftes Prozessverhalten aufzeigen sollen. Die Auslegung von Wave-Schnecken erfordert jedoch ein stärkeres Verständnis über das geometrieabhängige Prozessverhalten in der Extrusion. Im Rahmen der Dissertation werden zwei Themengebiete angegangen. Das erste Thema ist die Herleitung einer Methode zur Charakterisierung des Abbauverhaltens von Thermoplasten sowie die Nutzung der Charakterisierung als Vorhersagemodell. Das zweite Thema behandelt die Auslegung von Wave-Schnecken basierend auf numerischen Simulationen samt Validierung anhand von sieben Energy-Transfer-Schnecken im Vergleich zu drei konventionellen Schnecken. Hierbei werden unter anderem der Materialabbau, die thermische und die stoffliche Homogenität betrachtet, um ein umfassendes Bild über das Prozessverhalten der Schnecken zu schaffen. Die vorgestellten Untersuchungen dienen schlussendlich zu einer Bestätigung des vorteilhaften Prozessverhaltens von Wave-Schnecken.

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Ein Beitrag zur Erarbeitung von Fertigungsrichtlinien für das Kunststoff Freiformen - Hirsch, Andre

Materialschonende Verarbeitung von Thermoplasten auf Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Experimentelle und simulative Analyse der Mischwirkung in Einschneckenextrudern - Schadomsky, Michael

Evaluation of the Influence of Particle Type, Shape and Size on the Thermal Conductivity of Filled Polymers in the Fused Filament Fabrication Process - Moritzer, Elmar; Elsner, Christian Lennart
The Fused Filament Fabrication (FFF) process is increasingly used for the manufacturing of individualized and complex structures, which continuously results in new requirements regarding the material properties. A characteristic material property for polymers is the low thermal conductivity. However, for specific applications, such as additively manufactured injection molding tool inserts, increased thermal conductivity is advantageous. In this study, the influence of fillers of different types, shapes and sizes on the resulting thermal conductivity of compounds is investigated. The aim is to analyze the effects of the fillers, considering the FFF-typical strand structure. The first step is to characterize the fillers in terms of shape and size. Based on this, the resulting thermal conductivity of specimens manufactured in the FFF process for different build orientations is specifically examined and compared to injection molding. This ensures that the process- and material-related anisotropy of the specimens is considered in the analysis. For the evaluation, a methodology is developed to be applied in Laser Flash Analysis (LFA), which allows the results to be evaluated despite the characteristic FFF surface structure. For the final visualization of the influence of the particle size on the particle orientation, Scanning Electron Microscopy (SEM) images of the relevant polymer compounds are made. The investigations provide a data basis regarding the influence of the particle type, shape and size on the thermal conductivity as well as for the requirement-oriented selection of fillers for processing thermally conductive polymer compounds in the FFF process.

Experimentelle und modellbasierte Untersuchungen zum Prozessverhalten von teilkristallinen Materialien im Spritzgießsonderverfahren GITBlow - Kröker, Michael

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Evaluation of the effects of different heating strategies on the joining partners during infrared welding of black polyamides - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J.

Evaluation of Infrared Welded Joints of Short Fiber Reinforced Thermoplastics Using Digital Image Correlation - Schöppner, Volker; Gevers, Karina; Schraa, L.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Proceedings of the 2023 International Conference on Composite Materials)

Entwicklung von Scale-Up-Regeln für das quasisimultane Laserdurchstrahlschweißen (QSS) von Thermoplasten - Schöppner, Volker; Arndt, Theresa (Joining Plastics)

Dielectric Heating in the Vulcanization Process of Rubber Extrudates - Schöppner, Volker; Petzke, J.

Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Simulation of Infrared Welded Short Fiber Reinforced Thermoplastic Parts based on Mori-Tanaka Homogenization Method - Schöppner, Volker; Gevers, Karina; Hoenen, N.; Uhlig, K.; Töws, P.; Decker, J.; Stommel, M. (Advanced Structured Materials)

Verbesserung der Betriebspunktauslegung durch Schneckensimulation - Schöppner, Volker; Austermeier, Laura; Trienens, Dorte (Wissenschaftlicher Arbeitskreis Kunststofftechnik)

The main factors influencing glass fiber shortening in the processing of bulk molding compounds (BMC) - Moritzer, Elmar; Scholle, Maximilian

Optimizing the Processing Performance of a Single Screw Extruder Using Live Simulations Based on Real Time Experimental Data - Köllermeier, Jonas; Schöppner, Volker

Schweißnahtkennwerte für die lebensdaueroptimierte Bauteilauslegung von hochtemperaturbeständigen Thermoplasten - Vogtschmidt, Sascha; Schöppner, Volker (Joining Plastics)

The Wave Must Be Right - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Plastic Insights)

Vorspannkraftrelaxation bei der Direktverschraubung additiv gefertigter Kunststoffbauteile - Moritzer, Elmar; Held, Christian

Einfluss von Infrarotschweißprozessparametern auf die quasistatische und zyklische Belastbarkeit von technischen glasfaserverstärkten Thermoplasten - Gevers, Karina; Töws, P.; Schraa, L.; Decker, J.; Schöppner, Volker; Uhlig, K.; Stommel, M. (11. Landshuter Leichtbau-Colloquium)

A NEW APPROACH FOR THE LOCAL DETERMINATION OF ENERGY INPUT IN CO-ROTATING TWIN SCREW EXTRUDERS BASED ON SCREW TORSION - Schöppner, Volker; Austermeier, Laura; Nordieker, A.

Development Of An Asymmetric Torque Model For The Two Screws Of A Twin Screw Extruder - Schöppner, Volker; Austermeier, Laura; Alsoud, A.

Auswirkungen unterschiedlicher Erwärmstrategien auf infraroterwärmte Polyphthalamide - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P.; Uhlig, K.; Stommel, M.; Decker, J. (Joining Plastics)

Devulkanisation schwefelvernetzender Elastomere im halbleitergestützten Mikrowellenverfahren - Schöppner, Volker; Petzke, J.

Investigation of the Volume Flow in the FFF Process as an Influencing Factor on the Resulting Orientation of Thermally Conductive Filler Particles - Moritzer, Elmar; Elsner, Christian Lennart; Deupmann, K.

Investigation of the influence of screw geometry on the resulting melt quality for cast film extrusion - Schöppner, Volker; Trienens, Dorte

Großflächig, komplex? InMould-Plasma ist die Lösung! - Moritzer, Elmar; Mühlhoff, Frederik Marvin; Rauen, Dennis; Kolbe, B.; Schlee, H.; Hokamp, C. (Kunststoffe)

Goodbye Hot Spots - with No Extra Energy Expenditure - Moritzer, Elmar; Kartelmeyer, Stephan; Kreamer, Dennis; Jaroschek, Christoph (Plastics Insights)

Hauptsache, die Wellenlänge stimmt - Schöppner, Volker; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

Hotspots ade - ohne Extra-Energieaufwand - Moritzer, Elmar; Kartelmeyer, Stephan; Kraemer, Dennis; Jaroschek, Christoph (Kunststoffe)

Optimization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian

Optimisation of the Simulation of Rubber Extrusion dies by means of the Integration of empirically determined characteristic Maps - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Wiesel, C.; Nillius, U.; Schön, M.; Limper, A. (KGK Kautschuk Gummi Kunststoffe)

Mischmaterialschweißen von PC/ABS und PMMA beim Warmgasstumpfschweißen mit Runddüsen - Schöppner, Volker; Gevers, Karina; Albrecht, M.; Seefried, A.

Microwave Heating of Rubber Extrudates - Petzke, J.; Kleinschmidt, Dennis; Schöppner, Volker

Konturnah kühlen für wenig Geld - Moritzer, Elmar; Kartelmeyer, Stephan; Kringe, Roberg; Jaroschek, Christoph (Kunststoffe)

Investigation regarding the correlation of the relative influences during the extrusion process of cast films on the residual melt quality - Schöppner, Volker; Trienens, Dorte

Material-Preserving Extrusion of Polyamide on a Twin-Screw Extruder - Schöppner, Volker; Altepeter, Matthias; Schall, Christoph Wilhelm Theodor; Wanke, Sven; Kley, Marina (Polymers)

Modellierung der Feststoffförderung im Einzug von Nutbuchsenextrudern mit Hilfe von DEM-Simulationen - Brüning, Florian
Bei der Auslegung von Einschnecken-Plastifizierextrudern mit genutetem Einzug sind Simulationen ein gängiges Mittel, um zeit-, ressourcen- und kostenintensive experimentelle Untersuchungen einzusparen. Bestehende mathematisch-physi-kalische Berechnungsmodelle auf Basis analytischer Gleichungen weisen jedoch einige Annahmen und Vereinfachungen auf, die die Qualität der rechnerischen Vorhersage reduzieren können. Diese Arbeit liefert daher einen Beitrag, indem analytische Modelle zur Berechnung des Druck-Durchsatz-Verhaltens und der Antriebsleistung in genuteten Einzugszonen mithilfe von numerischen Simulatio-nen basierend auf der Diskrete-Elemente-Methode (DEM) überprüft werden. Es wird gezeigt, dass die Annahme eines gegendruckunabhängigen Durchsatzver-haltens sowie die Unterscheidung in form- und reibschlüssige Förderfälle ge-rechtfertigt ist. Die Annahme einer Blockströmung ist oft nicht gerechtfertigt, auch wenn dies nicht notwendigerweise zu Abweichungen in der Durchsatzberech-nung führt. Für die analytische Durchsatz- und Leistungsberechnung werden re-gressionsbasierte Korrekturfaktoren eingeführt, die die Vorhersagegenauigkeit steigern. Weiterführende Untersuchungen zeigen, unter welchen Bedingungen und mit welchen Maßnahmen sich der Durchsatz von genuteten Einzugszonen steigern lässt. Schließlich wird eine Methode zur Kalibrierung von DEM-Simula-tionen vorgestellt, mit welcher sich die Abbildungsgenauigkeit des tribologischen Verhaltens des Schüttguts erhöhen lässt.

Untersuchung der UVC-Bestrahlung als Oberflächenvorbehandlungsmethode von Polycarbonaten zur Erzeugung einer Verbundhaftung zu Flüssigsilikonkautschuken - Hartung, Michael

An approach for the numerical calculation of the non-isothermal pressure-throughput-characteristics of single screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of the influence of process and screw configurations on fiber length for recycled carbon fiber - Malatyali, Hatice; Schöppner, Volker; Hoemann, Theresa (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Investigation of shear rates in twin-screw extruder using CFD-simulation - Malatyali, Hatice; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Influence of fiber geometry and sizing on glass fiber breakage - Bürenhaus, Franziska Isabelle; Moritzer, Elmar (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Investigation of the Deposition Velocity Related Temperature Deviations for High Temperature Materials in the FDM Process - Moritzer, Elmar; Hecker, Felix; Knaup, Felix; Wächter, Julian (Proceedings of the 37th International Conference of the Polymer Processing Society (PPS-37))

Simplified numerical calculation of the isothermal, three-dimensional, Non-Newtonian flow characteristics of single-screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)